Pheochromocytoma/Paraganglioma (PPGL): A Misdiagnosed Cause of Hypertension during Pregnancy - Rafael Buck Giorgi; Priscila Teixeira Aroucha; Thalissa M. Favreto; Micaela F. Montero; Julia M. F. Velloni; Ilana Korkes; Elisa Napolitano Ferreira; Caroline Olivati; Jose Viana Lima; Claudio E. Kater; Flavia A. Costa-Barbosa (Hindawi Limited, 2024)
Hypertension (HT) during pregnancy is not an infrequent obstetric problem, reaching a prevalence of 5-10%. This condition is highly associated with both maternal and fetal complications if not precisely diagnosed and managed. Even though primary HT, obesity, and preeclampsia are the main causes of HT in this period, other less familiar conditions must be considered during the investigation. Pheochromocytoma and paraganglioma (PPGL) are chromaffin cell tumors that produce, store, and secrete catecholamines, leading to HT and other adrenergic manifestations. Recognition of PPGL is crucial since misdiagnosis and improper management can lead to high morbidity and mortality, particularly during pregnancy. We report on two cases of PPGL diagnosed during pregnancy with different managements. Case 1 is a 25-year-old female at 31 weeks of first pregnancy, whose severe HT and life-threatening symptoms prompted an emergency delivery without previous confirmation or medical treatment of a suspected PPGL. After confirmation, a right adrenal PPGL was surgically resected 4 months later, following 15 days of medical therapy. Case 2 is a 22-year-old female at 18 weeks of pregnancy whose symptomatic PPGL was resected in the second trimester. A next-generation sequencing panel, including 23 PPGL-related genes, found no germline pathogenic variants (GPVs) in case 1 and an exon 1-4 germinative heterozygous deletion of the MAX gene in case 2. Despite the different medical approaches, both cases had satisfactory outcomes. Although uncommon, PPGL should be considered in the differential diagnosis of HT in pregnancy since missing the diagnosis and failing to introduce appropriate and timely treatment may lead to dramatic consequences for the mother and fetus. PPGL diagnosed during reproductive age is likely to result from GPV, prompting genetic investigation and counseling.